Relationship Of Emotional Maturity With Social Interaction Of Student In SMP N 1 Ranah Batahan Pasaman Barat - Sri Wahyuni Mulia; Azrul Said (Universitas Negeri Padang, 2019)
This research is motivated by the phenomenon of many students who can not interact well in school, don’t respond well when invited to join their friends, even students express with anger, say harsh words, and even violence. One of the factors that influence emotional maturity is social interaction. The objectives of this study are (1) to describe the emotional maturity of students, (2) to describe the social interactions of students, (3) to examine the relationship between the emotional maturity of students and the social interaction of students of SMP N 1 Ranah Batahan. This research is a descriptive correlational type of research with quantitative methods. The population of this research is students at SMP N 1 Ranah Batahan. The sample size of 157 students was selected using the Purposive Random Sampling technique. The research instruments used were emotional maturity questionnaire and social interaction questionnaire. Data were analyzed with descriptive statistical techniques with the help of the SPSS For Windows 20.0 program. The results of this study reveal that (1) students emotional maturity is in the mature category, (2) students social interactions are in the good category, and (3) there is a positive significant relationship between emotional maturity ans students social interaction with an arithmetic value of 0,613. This shows that the value of r count > r table (0,156). These results then the hypothesis Hi: “there is a significant relationship between emotional maturity with social interaction of students in school” can be accepted and Ho is rejected.